P-744 Fertility intention for a second or third child among childbearing couple in Shanghai, China. (30th June 2022) - Zhu, C; He, C; Yan, L; Huirne, J.A; Mol, B.W; Zhang, J
Abstract: Study question: What is the intention rate and related factors for a second or third child among childbearing couple? Summary answer: Among couples with one child, 16.2% are willing to have a second child. Only 9.4% of couples with two children are pursuing third child. What is known already: The decline in fertility is becoming an inevitable trend in most countries around the world. In the end of 1970s, the one-child policy was implemented. Since 21 st century, China has gradually changed its fertility policy, from a selective two-child policy to a comprehensive two-child policy. Nevertheless, the number of total annual births in China has not shown an obviously increasing trend of growth. On August 20, 2021, the Chinese government amended the law to allow a couple to have three children. However, only a few studies have been conducted to evaluate fertility intention in the couples who already have kids. Study design, size, duration: We conducted a cross-sectional survey in Shanghai from July to August in 2021. This study population was based on the female fertility database established between 2013 and 2017, which contains basic sociodemographic information and the reproductive intentions. We conducted this study to evaluate the fertility intention of the second or the third child and its related factors. Participants/materials, setting, methods: From July to August in 2021, couples aged between 20 and 45 years old with one or two children was invited to participate in our study to give the information about "second/third births intention" and the factors that may probably related to it. Between the groups with and without second/third child intention, the chi-squared test and binary logistic regression was applied to compare the difference in the basic characteristics and relative factors. Main results and the role of chance: Among couples with one child, 130 (16.2%) couples had intention to have a second child. Only 9.4% of couples with two children show the desire to have a third child. The ideal number of children for all our participants was 1.72±0.52. And the ideal number of children among couples with one child is 1.61±0.52. By contrast, the ideal number for couples with two kids was 2.06±0.34. The study showed great differences in Socioeconomic and personal factors between two groups. For second-child intention, the female age over 35 years, first child's age over 7 years, annual payment for the first child ranges from 70, 000-100, 000 RMB and children's educational barriers were negatively associated with an intention to have a second child. Job with more free time makes it easier for couples to have a second child. Among couples with two children, parents with family financial constraints and children's educational barriers are less likely to have a third child. Fertility-encouraged government policy can promote couples to pursue a second or third child. It is necessary to take measures to reduce the burden of raising children and increase free time for couples to relief parent's pressure of rearing a child. Limitations, reasons for caution: As this is a single-center study in Shanghai, the sample size is relatively small. Although our sample size still meets the basic statistical requirements and can detect a moderate effect size as significance, the results may not be applicable to some other regions. Wider implications of the findings: The decision of fertility intention is influenced by female age, the first child's age, family economic conditions, children's education and national fertility policies. It is necessary to take measures to reduce the burden of raising children and increase free time for couples to relief parent's pressure of rearing a child. Trial registration number: ChiCTR2100045315